KLASIFIKASI DILALAH: ANALISIS DESKRIPTIF ATAS METODE PENUNJUKAN MAKNA DALAM ISTINBAT HUKUM ISLAM - Siti Rohani (Journal of Education, Teaching, and Learning, 2024)
This study examines the concept of dilalah in the perspective of Islamic law with a focus on the classification of dilalah as a method of indicating meaning in legal istinbat. Usul fiqh scholars define this discipline through two main approaches. First, the approach based on the structure of the wording (takribi idlafi), namely "ushul" and "fiqh". Second, the approach that understands ushul fiqh as a science that stands alone without looking at the composition of the words that form it. Etymologically, the word ushul is the plural form of ashl, which means "foundation" in both material and non-material aspects. While terminologically, ashl has five main meanings: (1) Legal basis (al-dalil), as in the statement that "the ashl of the obligation to pray is the Qur'an and Al-Sunnah", which shows that the dalil is the legal basis; (2) The foundation or basic principle (al-qa'idah al-kulliyah), as in the Prophet's statement which states that "Islam is built on five foundations (khamsatu ushul)", where ushul in this context means the basic principle; (3) The strongest (al-rajih), as in the ushuliyah rule "al-ashl fi al-kalam al-haqiqah", which means that the true meaning of a phrase is prioritized over the figurative meaning; (4) Branch or part (al-maqis alayh), as in the expression "al-khamr ashl li al-nabidz", which shows that khamar is the basis of analogy for the prophetz in terms of its prohibition due to its intoxicating nature; and (5) The application of the original law as long as there is no evidence that changes it (al-mustashhab), as in the rule "al-ashl al-thaharah", which stipulates that a person who has performed ablution remains in a state of purity until there is evidence that shows otherwise. This study uses a library research method with a descriptive-analytical approach, where data is collected from various classical and contemporary literature in the field of ushul fiqh to analyze how the concept of dilalah is used in determining Islamic law. The results of the study indicate that the first meaning, namely the legal basis (al-dalil), is the most commonly used meaning in the discipline of ushul fiqh and has important implications in the process of legal istinbat.